2021
DOI: 10.3390/atmos12101342
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Indoor Radon, Earthquake Magnitude Data and Lung Cancer Risks in a Residential Building of an Apulian Town (Southern Italy)

Abstract: (1) Background: The association of radon-222 with lung cancer is well studied. The aim of the study was to validate a model of indoor radon measurements, to apply radon software to estimate lung cancer cases that are attributable to radon and to study the relationship between radon and earthquakes. (2) Methods: Different data detectors were used to obtain radon measurements in different places. Continuous data collection and predictions of indoor radon concentrations were carried out. Software was used to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
2
1
Order By: Relevance
“…On average, the results found in this study are close to the values measured by Deiana et al [23] and by Vimercati et al [24] in their studies conducted in indoor hospital environments in Italy, for environments that are complying with established international standards. Also, it could be observed that the results obtained here are between 4 and 10 times lower than the values obtained by Vimercati et al [25] in their study that correlates lung cancer rates by exposure to radon gas in residential environments susceptible to seismic activities, also in Italy. This is indicative that in outdoor workplaces, radon can be considered a low risk to employees' health.…”
Section: Resultscontrasting
confidence: 77%
“…On average, the results found in this study are close to the values measured by Deiana et al [23] and by Vimercati et al [24] in their studies conducted in indoor hospital environments in Italy, for environments that are complying with established international standards. Also, it could be observed that the results obtained here are between 4 and 10 times lower than the values obtained by Vimercati et al [25] in their study that correlates lung cancer rates by exposure to radon gas in residential environments susceptible to seismic activities, also in Italy. This is indicative that in outdoor workplaces, radon can be considered a low risk to employees' health.…”
Section: Resultscontrasting
confidence: 77%
“…Therefore, the radon levels in the Apulia Region can be considered to be in the medium range. Other studies in the region investigated the correlation between an increased incidence of lung cancer and chronic exposure to radon [ 34 , 35 , 36 ]. The results of these studies confirm that indoor radon pollution is a significant concern throughout the whole region and is one of the primary causes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The published articles are intended to provide guidance and solutions for correctly measuring and evaluating radon in different environments and the efficient management of radon levels in affected buildings for radiation protection of the population. An attempt has been made to classify the contributions below [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]:  Three papers aim to define radon awareness and policy perspectives, to set-up radon specific norms to control of the health risk of radon exposure in the Republic of Moldova and to better define measurement procedures, approaches and standard guidelines for Romanian Schools.…”
mentioning
confidence: 99%